Glycemic Variability: Clinical and Prognostic Significance - Kenneth Yu Hsiang Lin; Kai-Ju Huang; Chun-Pai Yang (Diabetes Research, 2015)
Minimizing development or progression of chronic diabetic micro and macro-vascular complications has been always the goal of glycemic control. In recent years, much attention has been focused on the possibility that glycemic variability confers an additional risk factor for diabetic complications independent of glycated hemoglobin (HbA1c). Evidence suggests that fluctuating glucose levels produce endothelial dysfunction as well as an increase in free radicals, the key link between hyperglycemia and diabetic complications and that these changes are greater than those produced by sustained hyperglycemia in in vitro and in animal studies. In humans studies, experimental setting also support the hypothesis that plasma glucose fluctuations produce a higher increase in oxidative stress as well as endothelial dysfunction than those produced by sustained hyperglycemia in type 2 diabetes. Moreover, glycemic variability may have a role in the prediction of severe hypoglycemia, which may act as a precipitating factor of diabetic complications. Based on review of available evidence, we advocate decreasing hyperglycemia and diminishing glycemic variability as well as avoiding hypoglycemia in diabetic patients as targets of diabetic therapy. Future trials targeting the influence of the control of plasma glucose fluctuations on the development of diabetic micro-and macro-vascular complications are needed to further strengthen the evidence base.